2015
DOI: 10.5194/acp-15-6943-2015
|View full text |Cite
|
Sign up to set email alerts
|

On the competition among aerosol number, size and composition in predicting CCN variability: a multi-annual field study in an urbanized desert

Abstract: A 2-year data set of measured CCN (cloud condensation nuclei) concentrations at 0.2 % supersaturation is combined with aerosol size distribution and aerosol composition data to probe the effects of aerosol number concentrations, size distribution and composition on CCN patterns. Data were collected over a period of 2 years (2012–2014) in central Tucson, Arizona: a significant urban area surrounded by a sparsely populated desert. Average CCN concentrations are typically lowest in spring (233 cm−3), highest in w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 82 publications
(104 reference statements)
3
42
0
Order By: Relevance
“…3) with peaks between June–September. The trend of these parameters is in sharp contrast to anthropogenic tracers in the gas (CO, NO 2 ) and aerosol (EC) phases that are highest in winter months and lowest between May and August (Youn et al, 2013; Crosbie et al, 2015). These results suggest that DMA is more influenced by biogenic sources than anthropogenic sources in Tucson during months with higher temperatures, humidity, and plant growth.…”
Section: Resultsmentioning
confidence: 90%
“…3) with peaks between June–September. The trend of these parameters is in sharp contrast to anthropogenic tracers in the gas (CO, NO 2 ) and aerosol (EC) phases that are highest in winter months and lowest between May and August (Youn et al, 2013; Crosbie et al, 2015). These results suggest that DMA is more influenced by biogenic sources than anthropogenic sources in Tucson during months with higher temperatures, humidity, and plant growth.…”
Section: Resultsmentioning
confidence: 90%
“…Winter in the Tucson metropolitan area is characterized by enhanced residential burning for heat leading to increased PM 2.5 levels nearing exceedance of National Ambient Air Quality Standards [ Kramer et al ., ]. As the area is surrounded by mountains with strong boundary layer inversions during cold nights, residential burning emissions are trapped in a shallow layer and often are not ventilated in periods of prolonged cooler temperatures [ Crosbie et al ., ], leading to the highest year‐round PM 2.5 mass concentrations of species linked to biomass burning, which include elemental carbon, organic carbon, and water‐soluble organic carbon [ Youn et al ., ]. While it cannot be proven unambiguously that GFs less than 1 in Tucson are due to biomass burning, certainly, the overlap in time of burning during periods with these data points supports the case for a potential link.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Crosbie et al . [] reported that the lowest hygroscopicity values correspond with the maximum concentrations of EC and OC, which they found in the early morning in Central Tucson. On the other hand, during nighttime, internally mixed aerosols dominated by sulfate increased the hygroscopicity of particles during P1 in this study (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…Many of the previous studies showed diurnal cycles of particle hygroscopicity, with peaks typically appearing in the afternoon in urban [ Crosbie et al , ], rural [ Cerully et al , ], marine [ Kalivitis et al , ], boreal forest, and grassland areas [ Paramonov et al , ]. This has been explained by atmospheric aging of aerosols through condensational growth of photochemically oxidized organics and sulfate.…”
Section: Resultsmentioning
confidence: 99%